LEADERSHIP CHALLENGES OF SCHOOL PRINCIPALS IN IMPROVING TEACHER DISCIPLINE AT SD NEGERI 2 WAKAN, WAKAN VILLAGE, JEROWARU DISTRICT, EAST LOMBOK REGENCY, WEST NUSA TENGGARA. - Pashurrahman; Meilina Bustari (RADJA PUBLIKA, 2026)
This study aims to analyze the leadership challenges faced by school principals in improving teacher discipline at SD Negeri 2 Wakan, Jerowaru District, East Lombok Regency, West Nusa Tenggara, and to identify the strategies implemented and their impact on teacher discipline. This study employed a qualitative approach with a descriptive design. Data were collected through interviews, observations, and documentation involving the school principal, teachers, and relevant stakeholders as informants. The findings revealed that the principal faced internal challenges, including uneven discipline awareness and fluctuating teacher motivation, as well as external challenges such as the distance between teachers’ residences and the school, environmental factors, and the need to strengthen the school discipline culture. To address these challenges, the principal implemented leadership strategies including exemplary leadership, participatory approaches, open communication, professional development, and direct supervision. Exemplary leadership was found to be the most effective strategy in improving teacher discipline. The implementation of these strategies resulted in improved teacher discipline and professionalism, the development of a positive school discipline culture, increased student discipline and learning motivation, and enhanced community trust in the school. This study highlights the critical role of school leadership in improving teacher discipline and educational quality.